2021
DOI: 10.3390/rs13091720
|View full text |Cite
|
Sign up to set email alerts
|

Fusing Precipitable Water Vapor Data in CHINA at Different Timescales Using an Artificial Neural Network

Abstract: Global climate change has noticeable influences on the water vapor redistribution in China, which is embodied by the fact that both wetting and drying tendencies were observed across China. This poses the necessity to monitor and understand the water vapor evolution in China. However, observations of water vapor from different techniques are subjected to systematic biases, different spatiotemporal resolutions and coverages, and different accuracy, which would hamper their joint use, potentially leading to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Also, this research indicated that the land cover types in the spatial domain greatly influenced the retrieval model and analyzed the model performance on different land cover types. Xiong, et al [24] utilized a similar method to fuse GNSS, MODIS, and REA5 PWV data in CHINA at different timescales, and validation results demonstrated that modifying the MODIS and ERA5 PWV at the monthly timescale results had the best accuracy. Jiang, et al [25] applied the back propagation neural network (BPNN) method to combine AMSR2 and GNSS data to retrieve PWV on the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this research indicated that the land cover types in the spatial domain greatly influenced the retrieval model and analyzed the model performance on different land cover types. Xiong, et al [24] utilized a similar method to fuse GNSS, MODIS, and REA5 PWV data in CHINA at different timescales, and validation results demonstrated that modifying the MODIS and ERA5 PWV at the monthly timescale results had the best accuracy. Jiang, et al [25] applied the back propagation neural network (BPNN) method to combine AMSR2 and GNSS data to retrieve PWV on the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Popular data fusion methods use the advantages of the high precision and high temporal resolution of GNSS PWV to fuse or calibrate it with PWV products with high spatial resolution [20,21]. For example, Xiong et al and Zhang et al used a general regression neural network (GRNN) to fuse GNSS PWV and ERA5 PWV from mainland China and North America; the deviation between them was well calibrated, and high-precision PWV products were obtained [22,23]. Liu et al and Bai et al used a linear fitting method to correct MODIS PWV and obtained higher-accuracy PWV products on the basis of ensuring high resolution [24,25].…”
Section: Introductionmentioning
confidence: 99%